Water quality and phytoplankton assessment in Batang Ai hydroelectric dam, Sarawak - Malinda, Auluck (Universiti Malaysia Sarawak (UNIMAS), 2009)
This study was carried out in the months of November 2008 and January 2009 to assess the water quality and phytoplankton composition in Batang Ai Hydroelectric Dam, Sarawak. A total of 15 water quality parameters were recorded at 5 sampling stations; S1, S3, S4 (areas with cage culture), S2 (area without cage culture) and S5 (inflow to the reservoir) at three different depths (surface, 14m, 27m). Assessment of phytoplankton was conducted by collecting water samples and sieving it through a 20μm sieve. Results for nutrients show that the range of ammonia (mg/L) was 0.000 to 0.833, for nitrate (mg/L) was 0.010 to 0.053, for nitrite (mg/L) 0.001 to 0.013, for orthophosphate (mg/L) 0.04 to 1.28 and silica (mg/L) was 1.47 to 14.27. orthohosphate was highest at S2 (1.28 mg/L) in November 2009. This was due to the phosphate found in feed where the water flows from cage culture are to S2. High silica content in November 2008 was due to the washing of aluminosilicate by rain from the water shed. Range for BOD5 (mg/L) was from 2.68 to 11.03, COD (mg/L) 2.0 to 19.7, TSS (mg/L) 2.667 to 23.533 where highest concentration was at S4 and chlorophyll-a (mgm-3) 0.246 to 2.629. The highest BOD5 content was recorded in S3 at 27m depth where the high decaying matter was due to the presence of cage culture. COD was generally lower in January 2009 due to the dilution from raise of water level. Chlorophyll-a was high at 14m depth as phytoplankton was reported to prefers thermocline. A total of 40 genera of phytoplankton were identified from the area. The lower amount of cyanobacteria genera in the water indicates that the water is clean and the reservoir is oligotrophic.